2002
DOI: 10.1111/j.1749-6632.2002.tb04165.x
|View full text |Cite
|
Sign up to set email alerts
|

A Single Exposure to Restraint Stress Induces Behavioral and Neurochemical Sensitization to Stimulating Effects of Amphetamine

Abstract: Evidence indicates that repeated exposure to stressful events sensitizes the motor and addictive effects of drugs of abuse in rats. Regarding a single exposure to one restraint stress, previous findings have shown that it is sufficient to induce behavioral sensitization to stimulating and reinforcing properties of abuse drugs (e.g., amphetamine and morphine), as measured by locomotor activity and conditioned place preference, respectively. It is well known that enhanced dopaminergic neurotransmission in the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 36 publications
(94 reference statements)
3
38
0
Order By: Relevance
“…The irregular pattern to d-AMPH observed 24 h after the stress session seems to be a characteristic response at this time point, as was shown in our previous studies (Diaz-Otañez et al, 1997;Pacchioni et al, 2002), while that observed 1 week after stress had a more regular and sustained pattern. The difference in the behavioral responses to d-AMPH after stress might be related to the clearly different d-AMPHinduced DA response underlying both the short-and the long-term stress-induced effects.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The irregular pattern to d-AMPH observed 24 h after the stress session seems to be a characteristic response at this time point, as was shown in our previous studies (Diaz-Otañez et al, 1997;Pacchioni et al, 2002), while that observed 1 week after stress had a more regular and sustained pattern. The difference in the behavioral responses to d-AMPH after stress might be related to the clearly different d-AMPHinduced DA response underlying both the short-and the long-term stress-induced effects.…”
Section: Discussionsupporting
confidence: 58%
“…To draw a parallel between the previous findings and the microdialysis experiments, we ran the locomotor activity assay in a different group of rats, and used a new set of activity monitors. The results (Figure 1a and Pacchioni et al, 2002). Restraint stress induced a higher DA release evoked by d-AMPH in NAcc core and shell subdivisions and CPu compared with those observed after Saline injection (Figure 2).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Needless to say, AMPH is an indirect dopaminergic agonist and one of the most frequently abused psychostimulants. Exposure to some stressors is known to result in behavioral and neuroendocrine sensitization to AMPH [24][25][26], a state which, according to some authors, may promote the development of psychostimulant dependence and addiction [27][28]. In the context of this hypothesis, the behavioral hyposensitivity to AMPH after CVP exposure becomes intriguing.…”
Section: Chemicals Doses and Drug Administration Proceduresmentioning
confidence: 99%
“…Its stimulation is, in fact, necessary for the sensitization of amphetamine (Battisti et al, 2000;Groning et al, 2004;Ohmori et al, 1994;Pacchioni et al, 2002;Vezina & Quen, 2000;Wolf et al, 1994), methylphenidate (Gaytan et al, 2000), cocaine ( Heusner & Palmiter 2005;Li et al, 2000;Kim et al, 1996;Rompré & Bauco 2006), apomorphine (Acerbo et al, 2004;Pacchioni et al, 2002;Voikar et al, 1999) and other dopamine mimetics (Kalivas, 1995;Rockhold, 1998), nicotine (Kelsey et al, 2002), morphine (Jeziorski et al, 1994;Trujillo, 2002) and ethanol (Broadbent & Weiemier, 1999;Camarini et al, 2000;Kotlinska et al, 2006), as well as several types of stress such as, for instance, 'restraint stress' (Pacchioni et al, 2002) and 'social defeat stress' (Yap et al, 2005).…”
Section: Memantine Prevents the "Bipolar-like Behaviour" Induced By Amentioning
confidence: 99%